An Analysis Phatic Expression on Hotel Transylvania Animated Movie - Tiara Putri Safira; Sofwan Arif Agil; Pratiwi Amelia (UM Purwokerto Press, 2024)
In contemporary filmmaking, the portrayal of emotions is pivotal, with phatic communication playing a crucial role. Phatic communication, involving verbal interactions aimed at maintaining social relationships rather than conveying information, enhances narrative and character development. This study examines phatic expressions in the animated film